A Study of Public Life in Two Housing Areas in Bursa - Şahin, Belkıs Ece; Tümer Yıldız, Hikmet Özge; DOSTOĞLU, NESLİHAN (My University, 2012)
In this study, two different housing areas in the urban fabric of Bursa have been analyzed for distinguishing the characteristics of public life. One of the two housing areas covered in the study is populated by lower-income groups, while higher-income groups generally live in the other; thus the chosen areas are completely different in socio-economic terms. Located in the eastern part of the city and known as Y ld r m, the first area started to develop gradually with the construction of a complex (külliye) by Sultan Y ld r m Beyaz t during the Ottoman era in late 14 century, which was surrounded with residential areas in time. With the th migration Bursa attracted as an industrial city after 1950s, the population of lower-income households grew significantly in the area. The second area, Bademli, is Bursa’s first suburban neighborhood populated by the houses of Bursa’s upper-income population. An evaluation of the two settlement areas shows us that although better physical conditions are prevalent in Bademli, social relations are more intense in Y ld r m. In fact, research made in Ahmet Taner K lal Square situated in Y ld r m has shown that there are close social relations among the residents of the area, while Bademli lags behind in terms of public life.
Keywords: Urban open space; Public life; Social integration; Residential area; Bursa